1995
DOI: 10.1192/bjp.166.6.699
|View full text |Cite
|
Sign up to set email alerts
|

Services for Younger Sufferers of Alzheimer's Disease

Abstract: NEWSoN-SMITH, J. (1983) Who cares for the adult brain damaged?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Community and residential services could make special provision for younger people with dementia, who are in danger of being overlooked while aged care services are increasing (Williams, 1995). While the low geographical density of presenile dementia militates against regional organization of services, other strategies such as supraregional centres, support groups focusing on younger people with dementia, telephone conferencing to link carers, allocation of special days in day centres and linkage with other groups such as young people with head injuries or AIDS may be useful.…”
Section: Discussionmentioning
confidence: 99%
“…Community and residential services could make special provision for younger people with dementia, who are in danger of being overlooked while aged care services are increasing (Williams, 1995). While the low geographical density of presenile dementia militates against regional organization of services, other strategies such as supraregional centres, support groups focusing on younger people with dementia, telephone conferencing to link carers, allocation of special days in day centres and linkage with other groups such as young people with head injuries or AIDS may be useful.…”
Section: Discussionmentioning
confidence: 99%
“…Six participants of the Amsterdam Meeting Centers project were aged under 60, compared to none in the control group. In The Netherlands, as in other countries (Newens et al, 1995;Williams, 1995), young AD patients (and their spouses) rarely use the regular day centers in nursing homes, because of the mean age of the participants (mostly elderly people) in those centers. The Amsterdam Meeting Centers project demonstrated that the young AD patients and their spouses were much less resistant to participation in the general community centers that are frequented by people of all ages.…”
Section: Discussionmentioning
confidence: 99%
“…The specific needs of younger people with dementia have tended to be neglected by service providers, only 12 NHS trusts have specialist services (Williams, 1995;Barber 1997;NHS Health Advisory Service, 1997). In 1995 Leeds Community and Mental Health Services NHS Trust, with the City of Leeds Department of Social Services, developed a multi-disciplinary community oriented early onset dementia team.…”
Section: Discussionmentioning
confidence: 99%